Gender Identification Based on the Parameters of the Sternum Bone in the Cadavers - Siamak Soltani (International Journal of Medical Toxicology and Forensic Medicine, 2020)
Background: Identifying identity in the absence of large bones becomes more difficult and complicated; accordingly, it is highly beneficial to use the features of the sternum. The present study aimed to evaluate the dimensions of the sternum and its relation with gender in the Iranian population. Methods: This cross-sectional study was conducted on 200 cadavers (100 men and 100 women). By performing an autopsy, the sternum bone was first cut in the midline using a vibrating saw, and the different dimensions were measured using a caliper. Results: Among different dimensions related to the sternum, the mean length of manubrium, mesosternum, the largest width of manubrium, and the shortest width of manubrium were significantly higher in men compared to women. Regarding the value of each sternal diameter in discriminating male and female gender, the highest discriminative value was specified to the shortest width of manubrium (cutoff: 26.75, sensitivity: 100%, specificity: 84.0%), followed by the length of sternebrae 1 (cutoff: 8.45, sensitivity: 76.0%, specificity: 21.0%). Conclusion: Measuring various indices of sternum bone, particularly the shortest width of the manubrium and the length of sternebrae 1, leads to gender identity accurately.